PENENTUAN PREMI TUNGGAL BERSIH ASURANSI JIWA BERJANGKA BERDASARKAN STATUS MULTIPLE DECREMENT - Fitriani Fitriani; Aprida Siska Lestia; Yuana Sukmawaty (EPSILON: JURNAL MATEMATIKA MURNI DAN TERAPAN, 2019)
Insurance is an attempt of risk diversion by the insured person to the insurance company. The risk is referred to the future event that will potentially cause a financial loss. Based on many risk factors,the status of insurance was divided into a single decrement and a multiple decrement. In single decrement, the only factor caused benefit payment is death, while in multiple decrement there is more than one factors caused benefit payment. As a consequence, beside the random variable of time until termination , there is another random variable appears that is the cause of decrement . The aim of this study was to describe the development process of a multiple decrement table and determine net single premium based on multiple decrement status. This study was conducted by describing the construction process of components in the multiple decrement table using joint distribution and marginal distribution for each random variable. This study is a various equation for constructing a multiple decrement table was obtained. That probability equation was also used to form the net single premium equation of term insurance based on multiple decrement status by using probability function of time until termination and cause of termination. Keywords: Term Insurance, Multiple Decrement, Net Single  Premium